Anteseden Yang Mempengaruhi Niat Pembelian Pada Jasa Pengiriman Makanan Online (Integrasi TBP, TPR, DAN ELM) - Rut Ria Widiawati; Rifelly Dewi Astuti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The Covid-19 pandemic has driven the expansion of Indonesia's digital economy. One of the emerging sectors is the hospitality industry and the online food delivery services included in it have been rapidly growing across Indonesia. Therefore, the elements that influence customer perception and purchase intention regarding OFDS must be better understood. Therefore, this study was created to examine perceived benefits (convenience, trust, order accuracy, and variety of choices), perceived risks (financial risks, product risks, security risks, time risks, social risks, and psychological risks), and online persuasion through central routes (argument quality) and peripheral routes (image appeal, navigation design, social presence, and connectedness) on consumer attitudes and purchase intention by integrating the theory of planned behavior, theory of perceived risks, and the elaboration likelihood model. Based on an online survey of 1002 participants living in Indonesia, it was found that perceived benefits, perceived risks, and online persuasion influence consumer attitudes and purchase intention. The paper also discusses areas of future research and theoretical and practical consequences. Keywords: Elaboration Likelihood Model; Online Food Delivery Services; Theory of Planned Behavior; Theory of Perceived Risks; Purchase Intention